Social currencies in the Ecuadorian economy: fundamentals and analysis of its importance at the global context - Oñate Paredes, Carlos Andrés; Aucancela López, José Carlos (SATHIRI, 2023)
Social currencies are alternative monetary payment tools, which are used to help the most vulnerable populations in several countries around the world, including Latin-America and Ecuador. Considering that its approach seeks to activate local economies through injecting liquidity, the investigation and analysis of this monetary technology takes relevance in the context of an economy with high rates of unemployment, poverty and under a dollarized regime as the Ecuadorian. The main objective of this research is to analyze the factors that determine the circulation of social currencies in Ecuador; for that purpose, this paper initiates with the description of its operation from economic science, followed by a broad review of its process and experience within Ecuador and Latin-American region. The results indicate that the current national monetary regulations are factors that have limited the circulation of social currency, prohibiting and punishing its use. This aspect could be one of the causes of the low number of beneficiaries of the systems implemented in Ecuador, a number that is even less significant when compared to the possible demand of users of these instruments at the country level.